Examining the Implementation of the Android Based Outpatient Online Queuing System - Meryadi, Ni Nyoman; Suardana, Ida Bagus Raka (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study aims to determine the implementation of the android-based online outpatient queuing system at the UPTD Bali Mandara Eye Hospital. To achieve the research objectives, a qualitative method with a phenomenological approach through in-depth interviews was used. The interviews involved 12 informants consisting of two registration staff, eight patients or users of online queues, the Head of the SIMRS Unit, and the Head of the SIMRS Subdivision and Hospital Reporting as well as triangulation. Based on the results of this study, it can be seen that the use of the online queuing system is still not optimal. It is because there are not many patients who know about the system, and they are not interested in using the online queuing system.